FOUR DOMINANT FACTORS INFLUENCING STUDENTS' MATHEMATICAL CURIOSITY - Juandi, Dadang; Farida, Nurul; Al Aziz, Saddam; Meinarni, Welli (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
Curiosity is a crucial aspect of mathematics learning, as it encourages exploration, deep understanding, and active engagement. However, existing instruments for measuring students’ mathematical curiosity are still limited and rarely tested for construct validity using robust statistical methods. This gap indicates a need for a valid measurement tool that can capture the multidimensional nature of mathematical curiosity. This study aims to develop and validate a measurement instrument for students' mathematical curiosity through an exploratory factor analysis (EFA) approach. The background of this study is based on the importance of curiosity in mathematics learning, which plays a role in encouraging exploration, and deep understanding, and improving students' learning performance. However, there are still few instruments that have been systematically developed and tested for construct validity in this context. This study involved 177 students of department of mathematics at Universitas Negeri Padang from the 2022 to 2024 intake. Data were collected through a questionnaire containing 14 statement items arranged on a Likert scale. The results of the EFA analysis showed that four main factors were formed with a KMO value of 0.805 and a Bartlett's Test significance of 0.000. The four factors are called Reflective Thinking Curiosity, Routine Challenge Curiosity, Analytical Pattern Curiosity, and Active Exploration Curiosity. These findings indicate that the developed instrument is statistically valid and able to describe the multidimensional dimensions of mathematical curiosity. The implications of this study provide an empirical basis for measuring and understanding mathematical curiosity as an important part of the mathematics learning process.